The Words of Affectivity. Affect, Category, and Social Evaluation Norms for 400 Polish Adjectives - Grzybowski, Szczepan J.; Wyczesany, Miroslaw; Cichecka, Hanna; Tokarska, Aleksandra (Frontiers in Psychology, 2021)
Emotional adjectives can be grouped into two main categories: denoting and connoting stable (personality) traits and denoting and connoting transient (mood) states. They relate closely to the concept of affectivity, which is a pervasive tendency to experience moods of positive or negative valence. They constitute a rich study material for personality and affect psychology and neuroscience. Thus, this study was designed to establish a normed list of emotional adjectives with ratings encompassing four dimensions: emotional valence (positive or negative), emotional arousal (low-arousing or high-arousing), category (state, trait, and hybrid), and social judgment (competence, morality, and mixed). The adjectives were preselected based on previous broad Polish norming studies, personality and mood questionnaires, and a dictionary study. The results of the study were drawn from 195 participants who rated 400 adjectives that were chosen based on similar linguistic variables, such as frequency and word length. The dataset measures were proven to be stable and reliable. Correlations between the emotional valence and state-trait, valence and competence-morality, and emotional arousal and competence-morality dimensions were found. The study was successful in preparing a dataset of well-categorized (state, trait, and hybrid) positive and negative adjectives of moderate to high arousal ratings. Since the words were matched on linguistic variables, the set provided useful material that can be readily used for research into the effects of the category and emotional dimensions on language processing and as a basis for new personality questionnaires and mood checklists. The dataset could also be seen as a supplement for broader sets of published normed materials in Polish that link emotion and language.